A Ferroelectric Metallomesogen Exhibiting Field‐Induced Slow Magnetic Relaxation. Issue 5 (16th December 2021) - Akiyoshi, Ryohei; Zenno, Hikaru; Sekine, Yoshihiro; Nakaya, Manabu; Akita, Motoko; Kosumi, Daisuke; Lindoy, Leonard F.; Hayami, Shinya
Abstract: Magnetoelectric (ME) materials exhibiting coupled electric and magnetic properties are of significant interest because of their potential use in memory storage devices, new sensors, or low‐consumption devices. Herein, we report a new category of ME material that shows liquid crystal (LC), ferroelectric (FE), and field‐induced single molecule magnet (SMM) behaviors. Co(II) complex incorporating alkyl chains of type [Co(3C16 ‐bzimpy)2 ](BF4 )2 (1 ; 3C16 ‐bzimpy=2, 2'‐(4‐hexadecyloxy‐2, 6‐diyl)bis(1‐hexadecyl‐1 H ‐benzo[ d ]imidazole)) displayed a chiral smectic C mesophase in the temperature range 321 K–458 K, in which distinct FE behavior was observed, with a remnant polarization (88.3 nC cm −2 ). Complex 1 also exhibited field‐induced slow magnetic relaxation behavior that reflects the large magnetic anisotropy of the Co(II) center. Furthermore, the dielectric property of 1 was able to be tuned by an external magnetic field occurring from both spin‐lattice coupling and molecular orientational variation. Clearly, this multifunctional compound, combining LC, FE, and SMM properties, represents an entry to the development of a range of next‐generation ME materials. Abstract : A multifunctional Co(II) compound exhibiting liquid crystal, ferroelectricity, and field‐induced slow magnetic relaxation behavior has been synthesized for the first time. The results provide new insights towards the development of a new category of magnetoelectric (ME) materials.